(untitled) - Wildi, Ernst (Amsterdam,Boston, 2004)
"If you already own - or are thinking of buying - a Hasselblad, there is much useful information here." - Amateur Photographer
Keywords: Hasselblad camera,Photography,Máy ảnh cảm biến,Chụp ảnh; Handbooks, manuals, etc.,Handbooks, manuals, etc.,Sách hướng dẫn, cẩm nang,Sách hướng dẫn, cẩm nang